POLA KOMUNIKASI PENGASUH DAN ANAK ASUH DALAM PENGEMBANGAN BAKAT MINAT DI SOS CHILDREN'S VILLAGE DESA TARUNA MEULABOH KABUPATEN ACEH BARAT - Siti Hajar; Reni Kumala Sari (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2020)
The environment which humans grow and develop is inseparable from the communication process. Everyone has a different way of conveying message that can be understood. Caregivers in lieu of parent at the Orphanage have a big responsibility in educating foster children. Certainly have a good communication pattern in order to develop their talents and interests to be better than before. This study examines SOS's Children Village of Taruna Meulaboh, Aceh Barat District. This study aims to determine the pattern of communication between caregivers and foster children in the development of talents in SOS Children's Village of Taruna Meulaboh, Aceh Barat District. The research is using a qualitative approach. The method of data collecting is using Interview and documentation. The subject of this study were chairman of SOS Children's Village of Taruna Meulaboh and 2 (two) caregivers from different rooms, while the object of study was all data information relevant to communication pattern. The results show that communication pattern used by SOS Children's Village of Taruna Meulaboh is using interpersonal communication, public communication, and group communication. Three pattern deducted an effect on children insight and make it easier for children to hone their talent and interest.